2017
DOI: 10.1002/ajh.24641
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained isolated hyperferritinemia without iron overload

Abstract: Although hyperferritinemia may be reflective of elevated total body iron stores, there are conditions in which ferritin levels are disproportionately elevated relative to iron status. Autosomal dominant forms of hyperferritinemia due to mutations in the L2ferritin IRE or in A helix of L2ferritin gene have been described, however cases of isolated hyperferritinemia still remain unsolved. We describe 12 Italian subjects with unexplained isolated hyperferritinemia (UIH). Four probands have affected siblings, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…13,50 In addition, the levels of serum ferritin, which is mainly composed of L-chains, increase markedly in response to iron overloading. [51][52][53] Cohen et al have reported that renal PT and macrophages are the main sources of circulatory ferritin, 9 and marked increases in both serum ferritin and the renal expression of the L-chain were also observed in mice following the deletion of the H-chain gene in the PT. 54 AKI similarly resulted in a significant decrease in the H-chain of hepcidin knockout mice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,50 In addition, the levels of serum ferritin, which is mainly composed of L-chains, increase markedly in response to iron overloading. [51][52][53] Cohen et al have reported that renal PT and macrophages are the main sources of circulatory ferritin, 9 and marked increases in both serum ferritin and the renal expression of the L-chain were also observed in mice following the deletion of the H-chain gene in the PT. 54 AKI similarly resulted in a significant decrease in the H-chain of hepcidin knockout mice.…”
Section: Discussionmentioning
confidence: 99%
“…We, therefore, speculate that acute iron overloading may either induce disassembly of both ferritin chains, and/or paradoxically upregulate the L-and inhibit the H-chain expressions in renal tubular cells followed by the release of L-chain into systemic circulation, thus, resulting in the observed inverse relationship between serum and renal tissue ferritin. 9,13,51,52 In contrast, chronic iron overload may offer the necessary time for renal cells to compensate for the excessive intracellular accumulations of reabsorbed iron together with the release of the L-chain into circulation by increasing the production of both ferritin chains. 42,55 Hepcidin is the main iron regulatory hormone through its receptor, FPN, and both molecules are expressed by renal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the IRE region of the 5'UTR L-ferritin mRNA that disrupt the irondependent post-transcriptional regulation of L-ferritin (hereditary-hyperferritinemia-cataract syndrome) and mutations in the first exon of L-ferritin gene that alter ferritin glycosylation and secretion in the blood (5,6). Recently, patients with unexplained hyperferritinemia not associated with iron overload and cataract and possibly inherited as a recessive trait, have been described, suggesting the existence of mutations in gene/s not directly implicated in iron metabolism that could affect ferritin secretion and turnover (167). Last, hyperferritinemia is a common manifestation of Gaucher's disease and can be the revealing cause of the disease in some patients (168).…”
Section: Biochemical Indicesmentioning
confidence: 99%
“…There are three known mutations in the N-terminal region of the FTL gene that cause benign hyperferritinemia [15]. Despite serum ferritin hyperglycosylation, no other harmful effects have been detected in patients with this disorder [16].…”
Section: Introductionmentioning
confidence: 99%